PENGARUH KEPEMIMPINAN TERHADAP KINERJA DOSEN TETAP DI UNIVERSITAS KATOLIK MUSI CHARITAS - Lina; Agustinus Riyanto; Theresia Widyastuti (Jurnal Keuangan dan Bisnis, 2018)
Improving the quality of higher education relates to the performance of lecturers in the field of education, research and publications, and community service. Improving the performance of lecturers requires the competence and commitment of the university leaders. This study aims to determine the effect of leadership on the performance of lecturers. The study was conducted at the Musi Charitas Catholic University. The location of this research was conducted at two campuses of Musi Charitas Catholic University namely: Bangau Campus and Burlian Campus. The study was conducted for 8 months (September 2017 s.d April 2018). This study used a combination of exploratory research and explanatory research. Exploratory research aims to explore the phenomena of leadership factors that can improve the performance of tridarma for permanent lecturers at the Musi Charitas Catholic University Palembang. Explanatory research is to explain the relationship between research variables that are the influence of leadership variables on the performance of permanent lecturer of the Catholic University of Musi Palembang. Regression analysis was used to examine the influence of leadership on lecturer performance. The result of this research showed that the influence of leadership on lecturer performance was 52,5% while 47,5% of lecturer's performance variable was influenced by other variables outside of this research, including government policy variable, motivation, and lecturer personality.